ANALISIS KEBIJAKAN PENERAPAN PENCEGAHAN ANTI BULLYING DI SEKOLAH DASAR - Nugraha, Efrina Salma; Alpian, Yayan; Prawiyogi, Anggy Giri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the implementation of anti-bullying prevention policies at SDN Palumbonsari I. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of this study indicate that SDN Palumbonsari I, in anticipating bullying actions, has an anti-bullying policy that includes points of violations. There are posters around the school environment about the negative impacts and the definition of bullying. The school conducts socialization activities, organizes many positive activities, and collaborates with external parties such as the local military, supervising officers, the local government, and parents of students.